Bacterial biofilm interactions with human immune cells - Lee, Kelly (2023)
The human immune system is vast, and ranges from physical barriers to cellular mediators which coordinate to protect the host from the environment and pathogens. Bacterial cells have been shown to interact with various immune receptors which contribute to pathogen recognition, clearance and memory. Importantly, C-type lectin receptors (CLRs) interact with polysaccharides and are involved in the innate stages of immune recognition and decision-making during infection. Specifically, the CLRs MR, Dectin-2 and DC-SIGN all interact with high-mannose structures, which are abundant in multiple pathogens. Pseudomonas aeruginosa is a ubiquitous, Gram-negative bacterium that causes opportunistic infection in immunocompromised hosts, and is particularly associated with both diabetes and cystic fibrosis patients. Additionally, Staphylococcus aureus is a commensal organism and a common resident of the skin microbiome. P. aeruginosa and S. aureus pose a burden to the global healthcare system as ESKAPE organisms, and possess the ability to switch between a planktonic, free-swimming growth mode to biofilm, characterised by development of bacterial communities within an extracellular matrix (ECM). Our lab has previously demonstrated that both P. aeruginosa biofilms and purified biofilm carbohydrates from PAO1 biofilm-overproducing mutants, are able to interact with CLRs DC-SIGN, MR and Dectin-2, which all play a role in early immune decision making and modulation. During this study, we were able to optimise assays to confirm binding of these lectins to ECM polysaccharides from P. aeruginosa, namely Pel and Psl, as well as introduce a new species, S. aureus (SH1000), into our in vitro biofilm model which displayed potential GalNAc ligands. Due to binding artifacts identified in the culture medium, P. aeruginosa biofilm growth was optimised in DMEM-BSA. Binding of all three CLRs was maintained for whole biofilms in this new medium, but to purified product, only DC-SIGN binding was observed. Optimisation of this work is ongoing. To investigate cellular interactions during infection, a 3D co-culture model using a skin-like collagen matrix was designed and optimised to investigate interaction of human immune cells (monocyte-derived dendritic cells, moDCs) with P. aeruginosa (PAO1) biofilms in the context of cytotoxicity, cytokine production and surface marker expression. In this model, moDCs maintained high viability up to 24 h when cultured with live bacteria, although cytokine profiles were altered in the presence of bacteria. Specifically, chemoattractant protein MCP-1 was specifically downregulated in the presence of bacteria compared to other inflammatory cytokines (TNF-α, IL-1β) which were upregulated in the same conditions. Neither cytotoxicity nor cytokine profile was altered in the absence of DC-SIGN, indicating a certain level of redundancy in this context, contrary to earlier binding data. Additionally, surface markers (HLA-DR, CD11b, DC-SIGN, MR) were downregulated in the presence of PAO1 compared to uninfected cells when analysed by flow cytometry. After further investigation, this reduction was shown to be independent of secreted bacterial proteases, LPS stimulation or the general interaction of collagen with the immune cells. The findings displayed during this study have provided novel contributions to our understanding of the immune response to bacterial biofilms, in context of polysaccharide interaction with CLRs and whole biofilms with immune cells in a wound-like setting, and have given us some exciting insight into how bacteria modulate immune responses during chronic infection. Although not without limitations, the work conducted here provides some interesting routes for future investigation, potentially highlighting new avenues for therapeutic research and disease control.